Incidence of sternocutaneous fistulas following open heart surgery in a nationwide cohort - Steingrimsson, Steinn; Sjögren, Johan; Gudbjartsson, Tomas (Scandinavian Journal of Infectious Diseases, 2012)
We studied the incidence and characteristics of surgically treated sternocutaneous fistulas in a nationwide cohort of patients undergoing open heart surgery in Iceland. Between 2000 and 2010, sternocutaneous fistulas were treated surgically in 6 out of 2446 patients undergoing open heart surgery (incidence 0.25%, 95% confidence interval 0.11-0.53%). All patients were male, with a mean age of 71 +/- 9 y. In addition to antibiotic treatment, debridement of the wound was performed in all cases. Staphylococcus aureus and/or coagulase-negative staphylococci were identified as pathogens in 5 cases and Candida albicans in 1. Chronic infections developed in 3 patients who were treated repeatedly, 1 of them unsuccessfully. Inhospital stay ranged from 0 to 50 days (mean 19 days). Sternocutaneous fistulas are rare, but since they may have a devastating course, increased awareness of this infectious complication of open heart surgery is important.